2016
DOI: 10.1002/2015gl066796
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of bounce resonant scattering by fast magnetosonic waves

Abstract: In this study we present calculation of bounce resonant scattering of near equatorially mirroring electrons by fast magnetosonic waves. We first explore the sensitivity of the scattering rates and estimated time scales to a different number of resonances included into calculations. We then explore the sensitivity of calculated rates to the assumed wave normal angle. Our results show that at large radial distances bounce resonant scattering is capable of providing local isotropization of nearly equatorially mir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…Although EN emissions stay confined to the equatorial plane, they may propagate in radial/azimuthal directions (Chen & Thorne, ; Horne et al, ; Němec, Santolík, Pickett, Hrbáčková, et al, ; Santolík et al, ; Xiao et al, ). EN is considered to be important for electron dynamics in the Van Allen radiation belts (Bortnik et al, ; Horne et al, ; Li et al, ; Ma et al, ; Ni et al, ; Shprits, ; Walker, Balikhin, Canu, et al, ), as well as for the formation of so‐called butterfly distribution functions (Li, Bortnik, et al, ; Li, Ni, et al, ; Maldonado et al, ; Xiao, Yang, et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although EN emissions stay confined to the equatorial plane, they may propagate in radial/azimuthal directions (Chen & Thorne, ; Horne et al, ; Němec, Santolík, Pickett, Hrbáčková, et al, ; Santolík et al, ; Xiao et al, ). EN is considered to be important for electron dynamics in the Van Allen radiation belts (Bortnik et al, ; Horne et al, ; Li et al, ; Ma et al, ; Ni et al, ; Shprits, ; Walker, Balikhin, Canu, et al, ), as well as for the formation of so‐called butterfly distribution functions (Li, Bortnik, et al, ; Li, Ni, et al, ; Maldonado et al, ; Xiao, Yang, et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Roberts and Schulz [] obtained a theoretical diffusion coefficient, with the assumption that waves cover the whole bounce trajectory. Recently, Shprits [] found that magnetosonic waves might be a potential wave mode that can cause pitch angle scattering of near‐equatorially mirroring radiation belt particles through bounce resonance; the corresponding bounce resonance diffusion coefficient was evaluated by Shprits [] using Roberts and Schulz []. Note that magnetosonic waves are typically confined near the geomagnetic equator within 3°–5° in latitude [ Russell et al , ; Ma et al , ]; therefore, the Roberts and Schulz [] diffusion coefficient is valid only for particles whose mirror points are within the wave boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Additional mechanisms or more accurate descriptions of previously mentioned wave‐particle interactions are required to remove the near equatorially mirroring electrons. Recent studies have proposed such a class of candidate mechanisms, bounce resonance with magnetosonic or EMIC waves [ Shprits , , ; Chen et al , ]. Here we propose a new mechanism, nonlinear Landau resonance with EMIC waves, for the scattering of radiation belt electrons mirroring around the equator.…”
Section: Introductionmentioning
confidence: 99%